Before Peirce and Smith – The Manhes Converter: Its Development and Some Reflections for Today - Albert Pelletier; Phillip J. Mackey; Larry M. Southwick; A. E. (Bert) Wraith (The Minerals, Metals and Materials Society, 2009)
In 1881, the first commercial pneumatic Bessemer-type converter treating copper matte was successfully introduced by Pierre Manhes at the Eguilles copper plant near Vedène in France. This development followed over a year of testing on a smaller scale at a foundry in Vedène, during which the vertical tuyeres of the conventional Bessemer converter had been successfully replaced by horizontal tuyeres in an effort to avoid the freezing of copper which had occurred in the bottom of the vessel having vertical tuyeres. The Manhes Converter, as it became known, was the first successful large-scale adaptation of the Bessemer concept of using compressed air blown into a melt for metal refining and treatment. Within a few years, Manhes Converters utilizing horizontal tuyeres in either the original type of vertical converter, or a later and more enduring horizontal barrel converter, were in operation at over a dozen copper smelters around the world. It was this process that Messrs Peirce and Smith essentially improved with the introduction of the larger converter which bears their name and the development celebrated at this Symposium. The present paper briefly traces the original development by Pierre Manhes in the early 1880s and which set the stage for the later Peirce-Smith adaptation. The paper observes that the original development by Manhes was in part driven by the need to reduce coal (energy) consumption and hence the production cost in order for Eguilles to remain competitive with the larger plants in Swansea, Wales, where a ready supply of cheap coal helped keep smelter treatment terms of the day low. These themes are eerily resonant of today where booming copper production in China has impacted the industry, and also where energy consumption, closely linked to today’s more familiar theme of ‘climate change’ remains an important challenge currently confronting the entire industry. The paper concludes with comments on these seemingly parallel situations today and offers some thoughts for the future.